Glycemic Control as an Early Prognostic Marker in Advanced Pancreatic Cancer - Alpertunga, Ipek; Sadiq, Rabail; Pandya, Deep; Lo, Tammy; Dulgher, Maxim; Evans, Sarah; Bennett, Bridget; Rennert, Nancy; Frank, Richard C. (Frontiers in Oncology, 2021)
PURPOSE: Impaired glucose metabolism is present in most patients with pancreatic ductal adenocarcinoma (PDAC). Whereas previous studies have focused on pre-treatment glycemic indices and prognosis in those with concomitant diabetes, the effects of glycemic control during chemotherapy treatment on prognosis, in patients with and without diabetes, have not been well characterized. We examined the relationship between early glycemic control and overall survival (OS) in a cohort of patients with advanced PDAC treated in a community setting. PATIENTS AND METHODS: Seventy-three patients with advanced PDAC (38% with diabetes) receiving chemotherapy while participating in a biobanking clinical trial were included. Clinical characteristics and laboratory results during one year were obtained from the electronic medical record. Kaplan-Meier estimate, log-rank test and hazard ratios were computed to assess the effect of glycemic control on OS. The Cox proportional hazards regression model was applied to ascertain the significance of glycemic control with other survival variables. RESULTS: 1,418 random blood glucose (RBG) values were analyzed. In accord with previous findings, a 50% decline in the serum tumor marker CA 19-9 at any time was predictive of survival (P=0.0002). In univariate analysis, an elevated pre-treatment average RBG, three-month average RBG (RBG-3) and the FOLFIRINOX regimen were associated with longer survival. Based on ROC analysis (AUC=0.82), an RBG-3 of 120 mg/dL was determined to be the optimal cutoff to predict 12 month survival. In multivariate analysis that included age, stage, BMI, performance status, presence of diabetes, and chemotherapy regimen, only RBG-3 maintained significance: an RBG-3 <120 mg/dL predicted for improved OS compared to >120 mg/dL (19 vs 9 months; HR=0.37, P=0.002). In contrast, an early decline in CA 19-9 could not predict OS. CONCLUSION: Lower glucose levels during the first three months of treatment for advanced PDAC predict for improved OS in patients both with and without diabetes. These results suggest that RBG-3 may be a novel prognostic biomarker worthy of confirmation in a larger patient cohort and that studies exploring a possible cause and effect of this novel survival-linked relationship are warranted.